Comparison of temporomandibular joints in relation to ages and vertical facial types in skeletal class II female patients: a multiple-cross-sectional study - Jing Zhou; Huifang Yang; Qing Li; Weiran Li; Yi Liu (BMC, 2024)
Abstract Background The temporomandibular joint (TMJ) is closely related to the dynamic balance and stability of mandibular function and orthodontic treatment. Skeletal class II female patients are thought to be at high risk for TMJ disease. The relationship between the TMJ and craniofacial structures is still controversial. This study compared the morphology and position of the TMJ in skeletal class II adolescents and adults with various vertical facial types using cone-beam computed tomography (CBCT). Materials and methods A total of 117 skeletal class II patients were divided into three groups according to the FH-GoGn angle (hypodivergent, normodivergent and hyperdivergent), with 40 class I normodivergent patients serving as controls. Each group contained two age subgroups (adolescents: 11-14 years old, adults: 18-35 years old). The size (condylar length, height, long and short axis diameter, glenoid fossa width and depth) and shape (condylar neck inclination, condylar head angle and long axis angle, articular eminence inclination) of the condyle and fossa, joint space (anterior, superior, posterior, mesial and lateral), and position of the fossa (vertical, transverse, and anteroposterior distance) and condyle were measured and compared using CBCT. Results Class II hypodivergent patients exhibited the greatest condylar length, height, and long- and short-axis diameter; steepest articular eminence; deepest fossa depth; largest superior, mesial and lateral joint spaces; and highest fossa position in both age groups. The manifestations of class II hyperdivergent patients were mostly the opposite. In adults, except for the condylar long axis angle, the measurements of the condyle increased differently among skeletal patterns, while the measurements of the fossa decreased, as the joint spaces and fossa position remained approximately stable compared with those in adolescents. Conclusion The vertical skeletal pattern, rather than the class II sagittal skeletal pattern, may be the main factor affecting the morphology and position of the TMJ. Attention should be given to the TMJ area in hyperdivergent patients with a relatively poor-fit condyle-fossa relationship. The changes in the TMJ with age were mainly morphological rather than positional and varied with skeletal pattern.